Asphalt Jesus : - Elnes, Eric (Jossey-Bass, 2007)
Arizona pastor Elnes (United Church of Christ) had an idea that wouldn't go away: develop principles of a more generous and affirmative faith to counter the dominance of conservative Christianity in the media, and to witness for this faith by walking with other Christians 2,500 miles from Phoenix to Washington, D.C. Using as a guide these biblically based principles, emphasizing love of God, neighbor and self (described in his previous book The Phoenix Affirmations), Elnes recounts the cross-country journey as the walkers tried to spread the news that a vital alternative is flourishing in America's churches. The CrossWalk America travelers discovered extraordinary hospitality—and sometimes hostility—across surprising denominational lines as they searched for common ground with other Christians. The book shines when Elnes focuses on the walkers' encounters with people and churches in small towns across the U.S., but lags as he interprets biblical stories and discusses the Phoenix Affirmations. Less a narrative than a series of extended anecdotes, the book raises questions it doesn't answer about the walk and its impact on participants' faith. (Aug. 3)